Should We Fear Wipe-Out in Glaucoma Surgery? - Marco Zeppieri; Ludovica Cannizzaro; Giuseppe Gagliano; Francesco Cappellani; Lorenzo Rapisarda; Alfonso Spinello; Antonio Longo; Andrea Russo; Alessandro Avitabile (Diagnostics, 2025)
Wipe-out is defined as a sudden, unexplained, and irreversible loss of residual central vision following glaucoma surgery, typically in eyes with advanced visual field damage and severely compromised optic nerves. The purpose of this review is to critically assess the current incidence, risk factors, pathophysiological mechanisms, and clinical relevance of “wipe-out”, a rare but devastating complication of glaucoma surgery characterized by sudden, unexplained central vision loss postoperatively. A comprehensive literature review was conducted, analyzing key peer-reviewed studies from electronic databases (PubMed, Medline, and Google Scholar) published up to 2025. The data from the literature published prior to the year 2000 suggest that wipe-out incidences range broadly from <1% to 13%. Contemporary prospective studies and large-scale reviews indicate a significantly lower current incidence, frequently below 1%. Identified risk factors include severe preoperative visual field loss (especially split fixation), older age, immediate postoperative hypotony, and compromised optic nerve head perfusion. The proposed mechanisms involve acute vascular insults, ischemia–reperfusion injury, and accelerated apoptosis of already vulnerable retinal ganglion cells. Modern MIGS and refined trabeculectomy techniques exhibit notably lower wipe-out risks compared to historical data. The literature emphasizes preventive management, including careful patient selection, incremental intraocular pressure reduction, and minimally invasive anesthetic approaches. Although wipe-out syndrome represents a serious complication, its incidence in modern glaucoma surgery is minimal. The considerable benefits of contemporary surgical approaches—particularly MIGS—in preserving vision clearly outweigh this very low risk. Ophthalmologists should remain vigilant but confident in the safety and efficacy of modern glaucoma surgical techniques, emphasizing proactive intervention to prevent blindness rather than avoiding necessary surgery in consideration of the minimal risk of wipe-out.